Identification of a mutation in the para-sodium channel gene of the cattle tick Rhipicephalus (Boophilus) microplus associated with resistance to synthetic pyrethroid acaricides - Morgan, J.; Corley, S.; Jackson, L.; Lew-Tabor, A.; Moolhuijzen, Paula; Jonsson, N. (Elsevier, 2009)
Resistance against synthetic pyrethroid (SP) products for the control of cattle ticks in Australia was detected in the field in 1984, within a very short time of commercial introduction. We have identified a mutation in the domain II S4-5 linker of the para-sodium channel that is associated with resistance to SPs in the cattle tick Rhipicephalus (Boophilus) microplus from Australia. The cytosine to adenine mutation at position 190 in the R. microplus sequence AF134216, results in an amino acid substitution from leucine in the susceptible strain to isoleucine in the resistant strain. A similar mutation has been shown to confer SP resistance in the whitefly, Bemisia tabaci, but has not been described previously in ticks. A diagnostic quantitative PCR assay has been developed using allele-specific Taqman® minor groove-binding (MGB) probes. Using the assay to screen field and laboratory populations of ticks showed that homozygote allelic frequencies correlated highly with the survival percentage at the discriminating concentration of cypermethrin. © 2009 Australian Society for Parasitology Inc.